Evaluation of Virucidal Efficacy of Human Norovirus Using Combined Sprayed Slightly Acidic Electrolyzed Water and Ultraviolet C-Light-Emitting Diode Irradiation Treatment Based on Optimized Capture Assay for Quantitative RT-qPCR - Song, Hyeyeon; Dang, Yun-Mi; Ha, Sanghyun; Ha, Ji-Hyoung (Frontiers in Microbiology, 2022)
Slightly acidic electrolyzed water (SAEW), an effective non-thermal virucidal treatment, has been used widely to prevent infectious viral cross-contamination. Surface disinfection technologies using ultraviolet C-light-emitting diode (UVC-LED) irradiation have recently attracted considerable attention. The SAEW sprayer technique is an efficient approach of preventing the spread of infectious viral pathogens in the public healthcare sector. Therefore, we investigated a small-scale system comprising sprayed SAEW disinfection combined with UVC-LED irradiation to inactivate the human norovirus (HuNoV) in the environment. A stainless-steel surface was inoculated with a HuNoV genogroup II genotype 4 (GII.4) to achieve maximum reduction values of 3.21 log10 genomic copies. For optimal disinfection conditions, the Response Surface Methodology based on the Box-Behnken design revealed that the specific treatment conditions for inactivation of HuNoV GII.4 were SAEW droplet volume of 180 µL, 30 ppm Available Chlorine Concentration of SAEW, and UVC-LED exposure dose of 2 mJ/cm2. The results indicated that the combined disinfection treatment could efficiently prevent the spread of HuNoVs in environment. Furthermore, the quadratic polynomial equations of the 3D response surface can be employed to predict the effects of combined disinfection treatment on HuNoV contamination on environmental surfaces. Therefore, sprayed SAEW disinfection combined with UVC-LED irradiation proposed in this study may offer insights for designing optimal control strategies and techniques to prevent the transmission of infectious diseases, particularly HuNoV.